Factors Affecting Purchasing Intention by Using Mobile Shopping Applications in Malaysia - Kah-Boon Lim; Sook-Fern Yeo; Jin-Chee Wong (International Journal of Business and Society, 2020)
The increasing use of a smartphone to shop which is known as mobile commerce has become a new trend in the market. Majority of people have at least one smartphone in their hand due to the convenience of a smartphone. With the smartphone, smartphone users can easily download the mobile shopping applications and used the applications in their daily life. The main objective of this study is to investigate the factors affecting consumers’ purchasing intention with the use of mobile shopping applications in Malaysia. The five factors that included in this study are perceived enjoyment, perceived usefulness, perceived ease of use, perceived trust and social influence while purchasing intention is the dependent variable. A set of selfadministered questionnaires has been circulated to 200 target respondents in Malaysia for data collection purpose. The major findings of this research showed that all the five independent variables have a significant relationship with purchasing intention. In conclusion, this research may help the mobile shopping applications marketers deeply developed better strategies to improve their business plan.